Risk Factors and Outcomes of Thalidomide-induced Peripheral Neuropathy in a Pediatric Inflammatory Bowel Disease Cohort. Issue 10 (October 2017) - Bramuzzo, Matteo; Stocco, Gabriele; Montico, Marcella; Arrigo, Serena; Calvi, Angela; Lanteri, Paola; Costa, Stefano; Pellegrino, Salvatore; Magazzù, Giuseppe; Barp, Jacopo; Ghione, Silvia; Lionetti, Paolo; et al.
Abstract : Background: Thalidomide is an effective therapy in children with inflammatory bowel disease refractory to standard treatments, but thalidomide-induced peripheral neuropathy (TiPN) limits its long-term use. We aimed to investigate the risk factors and the outcome of TiPN in children with inflammatory bowel disease. Methods: Within a retrospective multicenter cohort study, we evaluated prevalence and evolution of TiPN. Clinical data and candidate genetic profiles of patients with and without TiPN were compared with detect predisposing factors. Results: One hundred forty-two patients were identified. TiPN was found in 72.5% of patients (38.7% clinical and instrumental alterations, 26.8% exclusive electrophysiological anomalies, and 7.0% exclusive neurological symptoms). Median TiPN-free period of treatment was 16.5 months; percentage of TiPN-free patients was 70.0% and 35.6% at 12 and 24 months of treatment, respectively. The risk of TiPN increased depending on the mean daily dose (50–99 mg/d adjusted hazard ratio 2.62; 95% confidence interval [CI], 1.31–5.21; 100–149 mg/d adjusted hazard ratio 6.16; 95% CI, 20.9–13.06; >150 mg/d adjusted hazard ratio 9.57; 95% CI, 2.6–35.2). Single nucleotide polymorphisms in ICAM1 (rs1799969) and SERPINB2 (rs6103) genes were found to be protective against TiPN (odds ratio 0.15; 95% CI, 0.03–0.82 and 0.36; 95% CI, 0.14–0.88, respectively). TiPN was the cause of drug suspension in 41.8% of patients. Clinical symptoms resolved in 89.2% of cases, whereas instrumental alteration persisted in more than half of the patients during a short follow-up. Conclusions: In children with inflammatory bowel disease, TiPN is common but mild and generally reversible. Cumulative dose seems to be the most relevant risk factor, whereas polymorphisms in genes involved in neuronal inflammation may be protective. Abstract : Supplemental Digital Content is Available in the Text.Article first published online 16 August 2017.